Usability in mobile learning application / Fatin Sarah Salim ... [et al.] - Salim, Fatin Sarah; Abu Bakar, Zuriana; Mohamad Noor, Noor Maizura; Mohemad, Rosmayati (Faculty of Information Management, 2022)
Nowadays, mobile phones and tablets are more widely available and less expensive. Thus, it is easier for students to obtain a device for their studies. Mobile learning or m-learning also benefited from this occurrence. Usability in an application is vital in catering to the various need of students to ensure immaculate learning conditions. This paper aims to find a connection between student performance and the usability of the application. This paper focuses on three (3) main usability criteria; user engagement, satisfaction, and ease of use. The findings indicate that there is an association between a usable application and student performance.